1996
DOI: 10.1017/s0004972700021936
|View full text |Cite
|
Sign up to set email alerts
|

On the cohomology of a class of nilpotent Lie algebras

Abstract: Let g denote a finite dimensional nilpotent Lie algebra over C containing an Abelian ideal a of codimension 1, with z £ g\a. We give a combinatorial descript tion of the Betti numbers of 0 in terms of the Jordan decomposition 0 = (^ dj i=i induced by ad(z)\ a . As an application we prove that the filiform-nilpotent Lie algebras arising in the case t = 1 have unimodal Betti numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…The last case corresponds to filiform algebras. It is well known [1] that filiform algebras play also an interesting role in the study of Betti numbers b i (g) of nilpotent Lie algebras g. They produce lower bounds for the Betti numbers. More precisely computations have shown that for any small n, there exists a filiform algebra f n such that b i (f n ) ≤ b i (g) for all i and all nilpotent Lie algebras g of dimension n. Such filiform Lie algebras very often do not admit any affine structure.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…The last case corresponds to filiform algebras. It is well known [1] that filiform algebras play also an interesting role in the study of Betti numbers b i (g) of nilpotent Lie algebras g. They produce lower bounds for the Betti numbers. More precisely computations have shown that for any small n, there exists a filiform algebra f n such that b i (f n ) ≤ b i (g) for all i and all nilpotent Lie algebras g of dimension n. Such filiform Lie algebras very often do not admit any affine structure.…”
Section: 2mentioning
confidence: 99%
“…For filiform Lie algebras however both conjectures are clear. Nevertheless the explicit determination of Betti numbers of filiform algebras leads to formidable combinatorial problems, see [1].…”
Section: Affine Cohomology Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…, n − 1 . According to [1], the cohomology of f n is given by a standard partition problem: let κ i denote the number of i-tuples (a 1 , . .…”
mentioning
confidence: 99%